The effect of low-trauma fracture on one-year mortality rate among privately insured adults with and without neurodevelopmental disabilities - Whitney, Daniel G. (Bone, 2019)
BACKGROUND: Individuals with neurodevelopmental disabilities (NDDs) have poor development and preservation of skeletal health throughout the lifespan, and are especially vulnerable to low-trauma fracture and post-fracture health complications. However, no studies have examined if adults with NDDs have greater post-fracture mortality risk compared to adults without NDDs. The purpose of this study was to determine whether adults with NDDs have greater 12-month mortality rates following a low-trauma fracture compared to adults without NDDs. METHODS: Data from 2011 to 2017 was leveraged from Optum Clinformatics® Data Mart; a nationwide claims database from a single private payer in the U.S. Data were extracted from adults (18+ years) with and without NDDs that sustained a low-trauma fracture between 01/01/2012-12/31/2016, as well as pre-fracture chronic diseases (i.e., cardiovascular diseases, cerebrovascular diseases, diabetes, chronic obstructive pulmonary diseases, cancer). Mortality rate was estimated for adults with and without NDDs, and the mortality rate ratio (RR) and 95% confidence interval (CI) was calculated. Cox regression was used to estimate hazard ratio (HR) and 95% CI for 1-, 3-, 6-, and 12-month post-fracture mortality rates between adults with and without NDDs after adjusting for age, sex, race, U.S. region, and pre-fracture chronic diseases. RESULTS: Mean age (SD) at baseline was 56.7 (20.6) for adults with NDDs (n=3749; 45.2% men) and 63.9 (19.2) for adults without NDDs (n=585910; 34.4% men). During the 12-month follow-up period, 182 adults with NDDs (mean age [SD]=69.8 [14.7]; 46.2% men) and 25456 adults without NDDs (mean age [SD]=78.9 [9.8]; 38.3% men) died. Crude mortality rate was not different between adults with and without NDDs for any time points (e.g., 12-months: 5.40 vs. 4.96 per 100 person years; RR=1.09; 95% CI=0.94–1.26); however, it was greater for adults with intellectual disabilities compared to adults without NDDs (RR=1.46; 95% CI=1.23–1.79). After adjustments, adults with NDDs had greater post-fracture mortality rates for 3-, 6-, and 12-month time points (e.g., 12-months: HR=1.46; 95% CI=1.27–1.69). When stratified by the type of NDD, adults with intellectual disabilities and adults with autism spectrum disorders, but not adults with cerebral palsy, had greater 12-month post-fracture mortality risk. When stratified by fracture location, lower extremities were associated with greater crude mortality rate (RR=1.69; 95% CI=1.22–2.35) and adjusted mortality risk (HR=2.41; 95% CI=1.73–3.35), while upper extremities were associated with greater adjusted mortality risk (HR=1.76; 95% CI=1.23–2.50) for adults with vs. without NDDs. CONCLUSIONS: Among privately insured adults with NDDs, low-trauma fracture is associated with greater mortality risk within 1 year of the fracture event, even after adjusting for pre-fracture chronic diseases. Study findings suggest the need for earlier fracture prevention strategies and improved post-fracture healthcare management.